2009
DOI: 10.1007/s10549-009-0642-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acrylamide intake and estrogen and progesterone receptor-defined postmenopausal breast cancer risk

Abstract: Acrylamide, a potential human carcinogen, has been discovered in a variety of heat-treated carbohydraterich food products. Previously, dietary acrylamide intake was shown to be associated with endocrine-related cancers in humans. We assessed the association between dietary acrylamide intake and risk of postmenopausal breast cancer stratified by estrogen and progesterone receptor status. This study was embedded within the Netherlands Cohort Study on diet and cancer, which was initiated in 1986 enrolling 62,573 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 27 publications
(28 reference statements)
2
43
1
Order By: Relevance
“…Recently, Burley et al (66) analyzed the associations between dietary acrylamide exposure and breast cancer within this cohort (66). Overall, dietary acrylamide exposure (highest vs. lowest quintile) was not associated with breast cancer risk (OR 1.16; 95% CI 0.88–1.52) (66), which is in agreement with other prospective cohort (13;16;19;56), and case-cohort (11;17) studies that have reported no associations for dietary acrylamide and increased risk of breast cancer. Stratified analysis by menopausal status revealed no significant associations for postmenopausal women (OR 0.97; 95% CI 0.68–1.39)(66), or premenopausal women (OR 1.47; 95% CI 0.96–2.27) (66).…”
Section: Evidence From Case-cohort Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…Recently, Burley et al (66) analyzed the associations between dietary acrylamide exposure and breast cancer within this cohort (66). Overall, dietary acrylamide exposure (highest vs. lowest quintile) was not associated with breast cancer risk (OR 1.16; 95% CI 0.88–1.52) (66), which is in agreement with other prospective cohort (13;16;19;56), and case-cohort (11;17) studies that have reported no associations for dietary acrylamide and increased risk of breast cancer. Stratified analysis by menopausal status revealed no significant associations for postmenopausal women (OR 0.97; 95% CI 0.68–1.39)(66), or premenopausal women (OR 1.47; 95% CI 0.96–2.27) (66).…”
Section: Evidence From Case-cohort Studiessupporting
confidence: 87%
“…Pedersen et al (17) analyzed NLCSDC data for acrylamide intake and risk of postmenopausal breast cancer stratified by receptor status. The acrylamide exposure was estimated from the baseline FFQs (17).…”
Section: Evidence From Case-cohort Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least nine studies provided information on dietary AA and breast cancer risk (Mucci et al, 2005;Pelucchi et al, 2006;Hogervorst et al, 2007;Olesen et al, 2008;Larsson et al, 2009a;Wilson et al, 2009bWilson et al, , 2010Burley et al, 2010;Pedersen et al, 2010). Moreover, one study (Olsen et al, 2012) analyzed survival from breast cancer in relation to pre-diagnostic AA-Hb and GA-Hb.…”
Section: Breast Cancermentioning
confidence: 99%
“…Incident invasive breast cancer cases were identified in each study through follow-up questionnaires and confirmed with subsequent medical record review (22,31,33), linkage with cancer registries (20,21,23,24,27,28,32,(34)(35)(36), or both (19,25,26,29,30). Mortality registries were also used in some studies to ascertain additional cases (19,20,22,25,26,29,33,35).…”
Section: Ascertainment Of Breast Cancer Casesmentioning
confidence: 99%